Mapeamento da Dinâmica da Cobertura e Uso da Terra na Bacia Hidrográfica do Rio São João, RJ / Mapping the Dynamics of Land cover and Land Use in the watershed of São João River, RJ - Vinicius da Silva Seabra; Carla Madureira Cruz (Sociedade & Natureza)
The landscapes are understood as result of the interaction between its natural elements and its permanentconditioned modifications, or not, by human intervention. Within this design, it is important to understandthe history of human actions/interventions on the surface, since many of the past changes defineprocesses occurring in the present, thus having a fundamental role in the organization of the geographicalspace. Therefore, the objective of this study was to analyze the landscape dynamics in the watershed ofSão João River (BHRSJ) over the last 35 years by mapping the evolution of the Landcover and Landuse.This analysis was based from thematic maps (1:100.000), generated by object-based classification,using an image from the Landsat 4 MSS satellite (1975) and 3 images from the Landsat 5 TM satellite(1985, 1995, 2010), all related to the dry period. The thematic maps generated were inserted into a GISenvironment, where were processed analyses that provided information for the understanding and mappingof the changes occurred in BHRSJ in the last 35 years and thus provided important elements for analyzing the evolution of the landscape in the whole area. The analyses performed from the evolutionmap of the Landcover and Landuse, and the quantification of changes in the last 35 years, allowed theidentification of important transformations, of which we highlight: the loss of natural hedges, the loss ofnatural water bodies and the emergence of new water bodies (artificial).